Analisis Data Hubungan Antar Variabel Pada Pengetahuan Swamedikasi - Mustofani, Dian; Hariyani, Hariyani; Afif, Ahmad; Oktaviasari, Dianti Ias; Ariadhita, Bagus Yuli (UJMC (Unisda Journal of Mathematics and Computer Science), 2024)
Linear regression is a data analysis method that is for determine relation on the variables. One of the uses of this analysis is that can used to determine which independent variable policies should be increased or decreased. Regression analysis has two types, that is name simple linear regression analysis and multiple linear regression analysis. This research discusses the use of multiple linear regression analysis to determine which independent variables influence mothers' self-medication knowledge in treating fever in children, with known three independent variables and one dependent variable. The regression analysis in this research shows that the mother's education level has an influence on self-medication knowledge with a percentage influence value of 27.9%.